Do biological maturity and performance influence the training load of track and field athletes? - Cruz, R.; Alves, D. L.; Domingos, P. R.; Freitas, J. V.; Werneck, F. Z.; Bertuzzi, R.; De-Oliveira, F. R.; Lima, J. R. P. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2019)
It is necessary to clarify if BM and track and field performance can modulate the perception about RPE-session. The purpose of the present study was to verify if biological maturity and track and field-specific performance can be associated with training load (RPE-session method). Seventy-five young athletes (13-15 years old) of both genders participated in the present study. The experimental protocol lasted seven consecutive days. Performance tests (75-m running, long jump, 250-m running, shot put and 1000-m running) were made on the first day. After 48 hours, five days of track and field training it was prescribed, each day represents a training of each performance test. All training sessions had the same duration (120 min). The value of the training load was obtained multiplying the RPE value with training session duration (in minutes). For girls, the training load of 250-m training was correlated with biological maturity (r = -0.36, p = 0.02, n = 37) and specific performance (r = 0.33, p = 0.04, n = 37). All other analyzes indicate that biological maturity and track and field-specific performance do not influence the training load based on RPE-session method. Training load based on RPE-session is not influenced by biological maturity and track and field-specific performance, therefore can be used to control the training load of young track and field athletes. To girls it is necessary a care to control the training sessions intensity of 250-m running.